HISTORICAL AND PEDAGOGICAL APPROACHES TO STUDYING THE ORIGINS OF THE KUNGARAT DYNASTY IN THE KHIVA KHANATE (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the origin of the Kungur dynasty, which played an important role in the history of the Khiva Khanate, based on a historical-pedagogical approach. The study interprets the formation of the Kungur dynasty, the process of coming to power, and their political and social activities as an educational tool in teaching history. It also provides a pedagogical justification for the opportunities for students to develop historical thinking, national identity, and patriotic feelings through historical events and individuals. The article reveals the importance of interdisciplinary integration, a competency-based approach, and the use of interactive methods in history education.